The education system of pakistan: A recipe to disaster? - Muhammad Sohaib Liaquat (Journal of Research in Social Science and Humanities, 2024)
Education is the matter of life and death for any country. Unfortunately, Pakistan has not been able to develop a stable, up to date and just education system in the country till now. From 1947 to 2023, many major steps have been taken by the government but its implementation has been poor and unsatisfactory. A detailed analysis of all the problems in our education system has been discussed below. Also the immediate solutions to these problems have also been provided.